The Potential of Active Compounds in Traditional Herbal Plants from Lombok for Their Use in Dyslipidemia - Christian, Steven; Abdiman, I Made Tobias; Amaliya, Annisa Risqi; Shofa, Dhiya Atsila; Balqis, Ananda Amirah; Sesariana, Mayumi Agestia; Ayunda, Rahmah Dara (Jurnal Biologi Tropis, 2024)
Dyslipidemia is a condition characterized by abnormal lipid levels in the blood, including total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides. This condition can lead to complications such as cardiovascular diseases and stroke. The purpose of this study is to explore the potential of herbal plants from the Sasak tribe, as recorded in Lontar Usada, for managing dyslipidemia. Lontar Usada documents various medicinal plants that are traditionally used by the Sasak people, making it essential to investigate their active compounds and how they influence lipid profiles. This research employs a qualitative approach, focusing on a literature review and analysis of the plants mentioned in Lontar Usada, followed by a biochemical evaluation of their active compounds and mechanisms in regulating lipid metabolism. The findings reveal that several plants listed in Lontar Usada contain bioactive compounds with potential lipid-lowering effects, supporting their traditional use in managing dyslipidemia. In conclusion, the study confirms that the plants from Lontar Usada could offer a natural alternative for dyslipidemia management, aligning with the high cultural acceptance and availability of these plants within the Sasak community.